Application of multifunctional silylenes and siliranes as universal crosslinkers for metal-free curing of silicones. Issue 14 (19th June 2020) - Herz, Fabian A. D.; Nobis, Matthias; Wendel, Daniel; Pahl, Philipp; Altmann, Philipp J.; Tillmann, Jan; Weidner, Richard; Inoue, Shigeyoshi; Rieger, Bernhard
Abstract : Multifunctional silacyclopropanes act as universal crosslinkers for PDMS-elastomers, which can react via ring-opening or silylene insertion. Abstract : Conventional industrial crosslinking of silicones is usually done by the well-established tin-catalysed condensation, platinum-catalysed addition or peroxide curing. We report the first application of highly reactive multifunctional silylenes as universal crosslinkers for catalyst-free curing of standard industrial silicones. The reactive silylene species is generated by thermal decomposition of stable silacyclopropane precursors and reacts with various functionalities of silicone building blocks in an addition reaction. Alternatively, the multifunctional silacyclopropanes can be ring-opened by nucleophilic compounds like siloxanols, which can also be employed for network formation with standard nucleophilic siloxanes. These new crosslinking methods are not dependent on non-recoverable Pt- or toxic Sn-catalysts and enable the production of clean, extractable-free elastomers. We describe the synthesis of multifunctional siliranes as model compounds and their application in silicone curing.